A Review of Termite Pheromones: Multifaceted, Context-Dependent, and Rational Chemical Communications - Mitaka, Yuki; Akino, Toshiharu (Frontiers in Ecology and Evolution, 2021)
Termite colonies, composed of large numbers of siblings, develop an important caste-based division of labor; individuals in these societies interact via intra- or intercaste chemical communications. For more than 50 years, termites have been known to use a variety of pheromones to perform tasks necessary for maintenance of their societies, similar to eusocial hymenopterans. Although trail pheromones have been chemically identified in various termites from ancestral species to descendant species, other types of pheromones have not been elucidated chemically or functionally. In the past decade, however, chemical compositions and biological functions have been successfully identified for several types of termite pheromones; accordingly, the details of the underlying pheromone communications have been gradually revealed. Termite pheromones originate mainly from cuticular hydrocarbons, defense substances, and antimicrobial agents; many of them have developed multifaceted roles in termite societies through parsimonious use for multiple purposes. These termite pheromonal communications are often eavesdropped or mimicked by social parasites and termitophagous predators to deceive the host termites. Here, we review the current knowledge of chemical compounds that termites use as pheromones, how termites regulate their social activities using these pheromones, and how parasites and predators intercept the pheromones. Furthermore, we discuss the multifunctionalization and biosynthetic processes of termite pheromones.